Contemporaneous financial intermediation - Markus Merz (Digital Finance, 2021)
Digital innovations in banking and payments recently have garnered a great deal of attention. Specifically, distributed ledger technology (DLT) has the potential to fundamentally change the roles and responsibilities of stakeholders in the financial sector. DLT is a novel and fast-evolving approach to record and share data, e.g., payment transactions, among members of a decentralized network. Using transaction cost theory, the paper examines how DLT will change the cross-border payment infrastructure. DLT can reduce the overall transaction costs potentially resulting in the disappearance of correspondent banks.
Keywords: E42; G21; O30; P51; 330; Distributed ledger technology; Cross-border payments; Transaction costs; Correspondent banking; Ripple; Intermediation